Impact of Dunning’s OLI paradigm on MNEs’ entry mode into Chinese market: Case study of M&S and Tesla - Xiao, Junyi (2017)
This paper endeavors to give an illustration on how OLI paradigm affect entry mode selection when MNEs entering into Chinese market. China, as one of largest emerging market, gained increasing focus for its potential development opportunities and enormous consuming power. Also, its unique advantage of low- cost labor attracted huge number of FDI. It also obtained attention from researchers. Effect from OLI paradigm has been updated and poured into fresh theories all the time, scholars try to break the barriers and periphery of each element of OLI and find potential effect on entry mode selection.